Implementation Design In the Creation of Companies In the 4.0 Technology Era - Anwar, Muhammad Rehan; Sari, Siti Nurindah; Maesaroh, Siti; Haryanto; Widada, Sugeng (Aptisi Transactions On Technopreneurship (ATT), 2022)
Industry 4.0 has been referred to as a new modern stage in which various developing technologies come together to deliver continuous innovation. After all, there is no understanding of how the organization does this innovation. After all, no one knows how the company performs this type of innovation. In this way, we expect to gain a better understanding of how Industry 4.0 ideas are accepted in assembly plants. We present a theoretical framework for this advancement, which we divide into two categories: front-end and base innovation. Front-end innovation considers four factors: smart manufacturing, smart products, a smart inventory network, and smart work, whereas basic advancement considers four factors: the internet of things, cloud administration, big data, and investigation. The sampling method, variable definition, sample and variance method, and data analysis are all used in this study. To focus on adopting these advancements, we reviewed 92 assembly organizations. Our findings imply that Industry 4.0 is linked to a fundamental embrace of front-end innovations, with Smart Manufacturing taking center stage. Our findings also suggest that implementing basic innovations is putting the organization to the test, given the sample in question still has very little knowledge and testing. We propose the creation of an Industry 4.0 innovation layer and demonstrate the extent of adoption of these advancements as well as their company-building ideas.